Strong presence of the high grain protein content allele of NAM-B1 in Fennoscandian wheat - Hagenblad, Jenny, J.; Asplund, Linnéa, L.; Balfourier, François; Ravel, Catherine; Leino, Matti W., M. W. (Theoretical and Applied Genetics, 2013)
ISI Document Delivery No.: 035MX Times Cited: 2 Grain protein content in wheat has been shown to be affected by the NAM-B1 gene where the wildtype allele confers high levels of protein and micronutrients but can reduce yield. Two known non-functional alleles instead increase yield but lead to lower levels of protein and micronutrients. The wildtype allele in hexaploid bread wheat is so far mainly known from historical specimens and a few lines with an emmer wheat introgression. Here we report a screening for the wildtype allele in wheats of different origin. First, a worldwide core collection of 367 bread wheats with worldwide origin was screened and five accessions carrying the wildtype NAM-B1 allele were found. Several of these could be traced to a Fennoscandian origin and the wildtype allele was more frequent in spring wheat. These findings, together with the late maturation of spring wheat, suggested that the faster maturation caused by the wildtype allele might have preserved it in areas with a short growing season. Thus a second set consisting of 138 spring wheats of a northern origin was screened and as many as 33 % of the accessions had the wildtype allele, all of a Fennoscandian origin. The presence of the wildtype allele in landraces and cultivars is in agreement with the use of landraces in Fennoscandian wheat breeding. Last, 22 spelt wheats, a wheat type previously suggested to carry the wildtype allele, were screened and five wildtype accessions found. The wildtype NAM-B1 accessions found could be a suitable material for plant breeding efforts directed towards increasing the nutrient content of bread wheat.